2018
DOI: 10.1002/gj.3133
|View full text |Cite
|
Sign up to set email alerts
|

Using dated molecular phylogenies to help reconstruct geological, climatic, and biological history: Examples from Colombia

Abstract: Attempts at historical reconstruction are based on limited data. We are more likely to produce accurate historical reconstructions by utilizing information from diverse sources and pooling data within the relevant research communities which will allow us to build up a moving picture of the geological, climatic, and biological evolution of our planet. We suggest that dated phylogenies of plants can contribute greatly to a better understanding of Earth history. Timing of phylogenetic splits of lowland restricted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 62 publications
4
8
0
Order By: Relevance
“…In addition, our results support a north to south uplift of the Colombian Andes (Florez, 2003), as diversification of Pseudopimelodus occurred in a sequential manner from older lower altitude diversification events to younger higher altitude diversification events, as was also reported in Neotropical plant species in Colombia (Richardson et al, 2018).…”
Section: Manuscript To Be Reviewedsupporting
confidence: 87%
See 1 more Smart Citation
“…In addition, our results support a north to south uplift of the Colombian Andes (Florez, 2003), as diversification of Pseudopimelodus occurred in a sequential manner from older lower altitude diversification events to younger higher altitude diversification events, as was also reported in Neotropical plant species in Colombia (Richardson et al, 2018).…”
Section: Manuscript To Be Reviewedsupporting
confidence: 87%
“…The Late Miocene divergence observed between lineage and the clade containing lineages and 5, agrees with the uplift of Eastern Cordillera (10 mya; Gregory-Wodzicki, 2000) that permanently divided the former foreland basin into the Magdalena and Llanos basins (Hoorn et al, 1995). However, the Eastern Cordillera was not a substantial orographic barrier, as there must have been a low-elevation fluvial corridor between the Magdalena Valley and the eastern Orinoco plains connecting these two geographic provinces (Richardson et al, 2018). This may explain the closer phylogenetic relationships detected between lineage 3 (haplotypes from Orinoco hydrographic zone) and the trans-Andean lineages 4 and 5.…”
Section: Manuscript To Be Reviewedsupporting
confidence: 64%
“…We also observed that predicted suitability patterns in the Amazon were mirrored in some parts of the Pacific when applying the distribution range of the Amazon. This could be because some taxa were present before the northwestern Andean mountain range uplifted (Richardson et al 2018). Our observations point to potentially new habitats for cacao CWR, however there are no records to validate this.…”
Section: Predicted Distribution Of Historical and Collected Taxamentioning
confidence: 76%
“…Phylogeographic inferences ( Figure 1F ) offer insights into how species (1) diversify ( Quintero and Wiens, 2013 ) and (2) face the effects of past thermal variation ( Jezkova and Wiens, 2016 ; Richardson et al, 2019 ) by boosting complex interactions such as species facilitation ( Wheeler et al, 2015 ), adaptive introgression, and hybrid speciation ( Coyne and Orr, 2004 ; Abbott et al, 2013 ; Payseur and Rieseberg, 2016 ; Marques et al, 2019 ). For instance, interspecific hybrids with intermediate niche requirements may rescue population’s gene pools in the face of climate change, while they can also display signals of heterosis for thermal adaption due to dominance on recessive alleles or overdominance via novel allele combinations ( Abdelmula et al, 1999 ; Leinonen et al, 2011 ).…”
Section: From Deep-time Genomic Consequences Of Thermal Shifts To Lonmentioning
confidence: 99%